Intrahippocampal Adeno-Associated Virus–Mediated Overexpression of Nerve Growth Factor Reverses 192IgG-Saporin–Induced Impairments of Hippocampal Plasticity and Behavior - Dobryakova, Yulia V.; Spivak, Yulia S.; Zaichenko, Maria I.; Koryagina, Alena A.; Markevich, Vladimir A.; Stepanichev, Mikhail Yu.; Bolshakov, Alexey P. (Frontiers in Neuroscience, 2021)
One of aspects of Alzheimer’s disease is loss of cholinergic neurons in the basal forebrain which leads to development of cognitive impairment. Here, we used a model of cholinergic deficit caused by immunotoxin 192IgG-saporin to study possible beneficial effects of AAV-mediated overexpression of nerve growth factor (NGF) in the hippocampus of rats with cholinergic deficit. Suspension of recombinant AAV carrying cassette with CAG-NGF-IRES-GFP or CAG-IRES-GFP (control) was injected into both hippocampi of control rats or rats with cholinergic deficit induced by intraseptal injection of 192IgG-saporin. Analysis of choline acetyltransferase (ChAT) immunostaining showed that NGF overexpression in the hippocampus did not prevent strong loss of ChAT-positive neurons in the septal area caused by the immunotoxin. Induction of cholinergic deficit in the hippocampus led to impairments in Y-maze and beam walking test but did not affect behavioral indices in the T-maze, open field test, and inhibitory avoidance training. NGF overexpression in the rats with cholinergic deficit restored normal animal behavior in Y-maze and beam walking test. Recording of field excitatory postsynaptic potentials in vivo in the hippocampal CA1 area showed that induction of cholinergic deficit decreased magnitude of long-term potentiation (LTP) and prevented a decrease in paired-pulse ratio after LTP induction and NGF overexpression reversed these negative changes in hippocampal synaptic characteristics. The beneficial effect of NGF was not associated with compensatory changes in the number of cells that express NGF receptors TrkA and NGFR in the hippocampus and medial septal area. NGF overexpression also did not prevent a 192IgG-saporin-induced decrease in the activity of acetylcholine esterase in the hippocampus. We conclude that NGF overexpression in the hippocampus under conditions of cholinergic deficit induces beneficial effects which are not related to maintenance of cholinergic function.